Neuroelectrostimulation on Adult Mice’s Back and Hip Muscles, Through a Special Vest: a Pilot Study - Cosin Shindo, João Vitor Tadashi; Rodokas, José Eduardo Petit [UNESP]; dos Santos Sousa, Guilherme; Maciel, Fabio Oliveira; Couto, Maira Cristina Rondina; Matsumoto, Mariza Akemi [UNESP]; Sangalette, Beatriz; German, Iris Jasmin Santos; Pomini, Karina Torres; Andreo, Jesus Carlos; Shinohara, André Luís (My University, 2021)
Introduction: neuromuscular electrostimulation (NMES) is a promising strategy for recovering muscle mass and function, including in elderly patients suffering from sarcopenia. We developed a vest with coupled electrodes to introduce electrostimulation throughout the body of young mice and verify the morphological changes in the scapular and pelvic region muscles. Material and Methods: a vest based on the semi-flexible resin was developed with the electrodes already attached, printed by 3D printing with connectivity to the Neurodyn III electrostimulation device (Ibramed ®). Based on this, six 14-weeks old C57BL/6 WT mice were used to conduct this pilot study. Results: After four weeks, we found that using the vest with the coupled electrodes was able to generate an increase in CSA in the gluteus and trapezius muscle compared to control mice (p<0.05). The gluteus of the experimental group (EG) hypertrophied 15% more than the control group (CG). As occurred in the gluteus, in the trapezius muscle, the CSA was 37% higher in EG than in CG. Conclusions: we conclude that this model of NMES in mice leaded to morphological changes in scapular and pelvic region muscles. For future work, we intend to include molecular and functional analyzes to evaluate if our model can reproduce the same functional effects reported in studies and afterward apply this model to elderly animals.
Keywords: Electrostimulation; Hypertrophy; Sarcopenia; Skeletal Muscle